Exhibition design - Locker, Pam (Lausanne, Switzerland AVA Publishing SA, 2011)
Basics Interior Design: Exhibition Design explores the role of the exhibition designer as a creative practitioner, and seeks to communicate a better understanding of the complexity of exhibition design as a discipline. Millions of people visit exhibitions of one sort or another every year, constituting a multi-billion dollar global industry. The umbrella term exhibition design incorporates the development of commercial trade fairs, brand experiences, themed attractions, world expositions, museum galleries, visitor centres, historic houses, landscape interpretation and art installations. Supported by case study examples and practical tips, this book offers a comprehensive guide to the practice of exhibition design, and considers the blurring of its borders with other design disciplines, such as graphic design.
What is an exhibition? Expos ; Commercial exhibitions ; Museum galleries ; Heritage ; Art and leisure -- Exhibition design. Exhibition families ; The role of the exhibition designer ; Exhibition space ; Designing for people ; Understanding the story -- Designing a narrative. Inspirational triggers ; Structure of narrative space ; Personal conversations ; Public conversations -- Exhibition media. Theatrical techniques ; Cinematic techniques ; Interactivity ; Display -- Exhibition graphics. Typography ; Graphic families ; Graphics and communication ; Graphic production ; Navigation -- Putting on a show. Sustainability ; Tendering ; Building an exhibition ; Exhibition lighting ; Handover ; Evaluation.
Keywords: Exhibitions--Design.; Exhibition buildings; Interior decoration